To solve the expression \(16x^2 - 1\) using the difference of squares pattern, we recognize that it can be factored as follows:
\[ 16x^2 - 1 = (4x)^2 - (1)^2 \]
This can be factored into:
\[ (4x - 1)(4x + 1) = 0 \]
Next, we set each factor to zero to find the solutions for \(x\):
-
\(4x - 1 = 0\)
- Solving for \(x\): \[ 4x = 1 \quad \Rightarrow \quad x = \frac{1}{4} \]
-
\(4x + 1 = 0\)
- Solving for \(x\): \[ 4x = -1 \quad \Rightarrow \quad x = -\frac{1}{4} \]
Thus, the solutions are:
\[ x = \frac{1}{4} \quad \text{and} \quad x = -\frac{1}{4} \]
Now, looking at the responses you provided, the correct solution(s) would be:
- \(x = -\frac{1}{4}, x = \frac{1}{4}\)
So, you would select the response that includes both of these values.